Pokdarwis Revitalization In The Development Of Kilalang Nagari Lubuak Batingkok Tourism Village - Ernawati, Ernawati; Tasrif, Nabila; Andres, Fran Serano (Universitas Negeri Padang, 2023)
Revitalization is the process of conserving or revitalizing something that was previously less powerful. The goal of this project is to restructure Kilalang tourism management and tackle difficulties that arise at tourist sites. This community service initiative is a cooperation between the Wali Nagari and the Lubuak Batingkok Village people. However, there are various difficulties in carrying out activities, one of which is that Pokdarwis has yet to be developed and executed in line with maximal job tasks and functions. Coordination with the Lubuak Batingkok Village Pokdarwis, shared commitment, mapping the potential and issues of Kilalang tourism, and implementation of the vision, mission, work plan, and regulations will be utilized as the approach method. Promotion, collaboration formation, and monitoring and evaluation are all part of the process.